Meniscus ECM‐functionalised hydrogels containing infrapatellar fat pad‐derived stem cells for bioprinting of regionally defined meniscal tissue. (19th December 2017) - Romanazzo, S.; Vedicherla, S.; Moran, C.; Kelly, D.J.
Abstract: Injuries to the meniscus of the knee commonly lead to osteoarthritis. Current therapies for meniscus regeneration, including meniscectomies and scaffold implantation, fail to achieve complete functional regeneration of the tissue. This has led to increased interest in cell and gene therapies and tissue engineering approaches to meniscus regeneration. The implantation of a biomimetic implant, incorporating cells, growth factors, and extracellular matrix (ECM)‐derived proteins, represents a promising approach to functional meniscus regeneration. The objective of this study was to develop a range of ECM‐functionalised bioinks suitable for 3D bioprinting of meniscal tissue. To this end, alginate hydrogels were functionalised with ECM derived from the inner and outer regions of the meniscus and loaded with infrapatellar fat pad‐derived stem cells. In the absence of exogenously supplied growth factors, inner meniscus ECM promoted chondrogenesis of fat pad‐derived stem cells, whereas outer meniscus ECM promoted a more elongated cell morphology and the development of a more fibroblastic phenotype. With exogenous growth factors supplementation, a more fibrogenic phenotype was observed in outer ECM‐functionalised hydrogels supplemented with connective tissue growth factor, whereas inner ECM‐functionalised hydrogels supplemented with TGFβ3 supported the highest levels of Sox‐9 and type II collagen gene expression and sulfated glycosaminoglycans (sGAG) deposition. The final phase of the study demonstrated the printability of these ECM‐functionalised hydrogels, demonstrating that their codeposition with polycaprolactone microfibres dramatically improved the mechanical properties of the 3D bioprinted constructs with no noticeable loss in cell viability. These bioprinted constructs represent an exciting new approach to tissue engineering of functional meniscal grafts.